Industrial servo control systems fundamentals and applications - Younkin, George W. (Fluid power and control, 1996)
Discussing how servo control theory can be employed to recognize and correct real world servo application problems, this work details the hardware specifications and servo drive classifications vital to the operation of machine servo drives. It emphasizes the importance of selecting the correct size servo drive for a given machine.